Repeated intravitreal injections of antivascular endothelial growth factor in patients with neovascular age-related macular degeneration may increase the risk of ischemic optic neuropathy - Chen, Yu-Yen; Chou, Pesus; Huang, Yu-Fang; Chien, Hung-Jen; Wu, Yu-Chieh; Lee, Chia-Chi; Huang, Li-Ying; Chen, Hsin-Hua (BMC ophthalmology, 2019)
Previous case reports have demonstrated the occurrence of ischemic optic neuropathy (ION) following intravitreal injections of antivascular endothelial growth factor (anti-VEGF). However, no previous studies have investigated the impact of injection numbers on the risk of ION. The aim of our study was to investigate whether repeated intravitreal injections of anti-VEGF would increase the risk of subsequent ION in patients with neovascular age-related macular degeneration (AMD). A population-based, retrospective cohort study using the Taiwan National Health Insurance Research Database was conducted from 2007 to 2013. Neovascular AMD patients receiving intravitreal injections of anti-VEGF during the study period were enrolled in the study cohort. Enrollees were divided into three groups according to the categorized levels of injection number (first level: < 10 times, second level: 10-15 times, and third level: > 15 times). Kaplan-Meier curves were generated to compare the cumulative hazard of subsequent ION among the three groups. Cox regression analyses were used to estimate crude and adjusted hazard ratios (HRs) for ION development with respect to the different levels of injection numbers. The confounders included for adjustment were age, sex, and comorbidities (diabetes, hypertension, hyperlipidemia, ischemic heart disease, and glaucoma). In total, the study cohort included 77,210 patients. Of these, 26,520, 38,010, and 12,680 were in the first-, second-, and third-level groups, respectively. The Kaplan-Meier method revealed that the cumulative hazards of ION were significantly higher in those who had a higher injection number. After adjusting for confounders, the adjusted HRs for ION in the second- and third-level groups were 1.91 (95% confidence interval [CI], 1.32-2.76) and 2.20 (95% CI, 1.42-3.43), respectively, compared with those in the first-level group. Among patients with neovascular AMD, those who receive a higher number of anti-VEGF injections have a significantly higher risk of developing ION compared with individuals who receive a lower number of injections.